DIPLOMASI FRONT de LIBERATION NATIONALE KANAK et SOCIALISTE (FLNKS) DALAM MENDAPATKAN DUKUNGAN KEMERDEKAAN DARI MELANESIAN SPEAREAD GROUP (MSG) - Dyah Ayu Salsabila; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study explains flnks strategy (Kanak and Socialist National Liberation Front) in gaining support to MSG (Melanesian Spearhead Group). It started with the Kanak people calling for a referendum that led to violence and conflict between pro-independence and anti-independence groups. This study uses pluralism perspective in international relations and group level of analysis supported by diplomacy theory using diplomacy approach that is public diplomacy and this study uses the concept of self-determination. This research is qualitative research with deductive analysis method.  The scope of research from this research is FLNKS diplomacy in obtaining support from MSG in 2015-2020.This research states that FLNKS diplomacy in obtaining independence support from MSG by means of forums conducted by FLNKS and MSG and tangible results reviewed from MSG's support in supporting FLNKS for New Caledonia independence internationally through the UN General Assembly.  Keywords: FLNKS, MSG, Pro-Independence, Self-Determination, Soft Diplomacy